2021
DOI: 10.1186/s12955-021-01817-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the German version of the needs assessment tool: progressive disease-heart failure

Abstract: Background The Needs Assessment Tool: Progressive Disease-Heart Failure (NAT: PD-HF) is a tool created to assess the needs of people living with heart failure and their informal caregivers to assist delivering care in a more comprehensive way that addresses actual needs that are unmet, and to improve quality of life. In this study, we aimed to (1) Translate the tool into German and culturally adapt it. (2) Assess internal consistency, inter-rater reliability, and test–retest reliability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The participants included in this qualitative study are a subsample of the patients included in the validation study of the German NAT: PD-HF ( 8 ). Since patients participated on a voluntary basis, patients who had negative experiences or felt that something was missing in their care may have been more inclined to participate in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants included in this qualitative study are a subsample of the patients included in the validation study of the German NAT: PD-HF ( 8 ). Since patients participated on a voluntary basis, patients who had negative experiences or felt that something was missing in their care may have been more inclined to participate in the study.…”
Section: Discussionmentioning
confidence: 99%
“…This is a secondary qualitative analysis of structured interviews undertaken within a larger study ( 8 ) to validate the German version of the Needs Assessment Tool: Progressive Disease—Heart Failure (NAT: PD-HF). After obtaining ethical approval (#2018-02175) for this analysis, we transcribed and thematically analyzed the longest interviews, as they were the most content-rich because participants engaged in deeper discussions with the interviewer.…”
Section: Methodsmentioning
confidence: 99%
“…It is a tool that is completed in <5 min and can guide physicians when assessing the PC needs of patients with HF and their relatives and help to identify those requiring specialist PC care. The German translation and validation has recently been published by our colleagues in the German-speaking region of Switzerland and we are now collaborating with them on the validation of the French translation ( 36 ). We believe implementing the NAT: PD-HF may help increase the number of HF patients receiving PC, based on their needs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we considered it important to highlight the importance of the complementary use of prognostic and needs assessment tools. Two recent systematic reviews [ 12 , 13 ] concluded that the most appropriate tool to assess needs in patients with HF is the Needs Assessment Tool: Progressive Disease – Heart Failure (NAT: PD-HF), which is available in English [ 33 ], Dutch [ 34 ], and German [ 35 ]. An example of a complementary use of prognostic and needs assessment tools could be to use the NAT: PD-HF as a routine screening tool for all patients upon entry into the HF program and annually, and in between, use prognostic tools such as the Surprise Question or the NECPAL tool.…”
Section: Discussionmentioning
confidence: 99%